If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(3x + 14) + 11 = 0 Reorder the terms: x(14 + 3x) + 11 = 0 (14 * x + 3x * x) + 11 = 0 (14x + 3x2) + 11 = 0 Reorder the terms: 11 + 14x + 3x2 = 0 Solving 11 + 14x + 3x2 = 0 Solving for variable 'x'. Factor a trinomial. (11 + 3x)(1 + x) = 0Subproblem 1
Set the factor '(11 + 3x)' equal to zero and attempt to solve: Simplifying 11 + 3x = 0 Solving 11 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 3x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + 3x = 0 + -11 3x = 0 + -11 Combine like terms: 0 + -11 = -11 3x = -11 Divide each side by '3'. x = -3.666666667 Simplifying x = -3.666666667Subproblem 2
Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Simplifying x = -1Solution
x = {-3.666666667, -1}
| 8+15-8= | | 35x+86=123 | | 5(z-5)+7z-4= | | 5+.75h=10 | | 4(x+2)=6(x-1)-2 | | x^4-8x^3+14x^2-4x-3=0 | | 3.4x=2.4x+5.0 | | -14=-7w | | 2(2p-3)-18= | | n-14=8n | | 0=1.77x+187 | | 4x^2-19+12=0 | | 9(3a+1)a=2 | | 2b-5-9b-3= | | (x+3)2=64 | | 24-1/2=0 | | 6x+10=-68-7x | | 0,4(2x-7)+1,2(3x+0,7)=1,6x | | 04(2x-7)+1,2(3x+0,7)=1,6x | | 12x-24=-36 | | z+4=-10 | | 12+8n=20 | | 8x^3+14x^2-4x= | | 9x-52=5x-8 | | -9(5x+6)+6= | | 7+6(u-6)+5u=2(5u+12) | | -2n+4(5-n)=2(2n+30) | | 2z+1/4=3/4 | | 5+2n=7-4n | | 2x+3-x-1=9x+4-6x-6 | | 2x-6x+7=2x+31 | | -3+5x+1-2x=-3+6x+5-4x |